Penerapan Algoritma Campbell Dudek Smith (CDS) untuk Optimasi Waktu Produksi Pada Penjadwalan Produksi - Mashuri, Chamdan; Mujianto, Ahmad Heru; Sucipto, Hadi; Arsam, Rinaldo Yudianto (JSINBIS (Jurnal Sistem Informasi Bisnis), 2020)
Research on optimizing production time using the dudek smith campbell algorithm (CDS) in scheduling the production process aims to makepan optimization for machine operations to produce 12 size griddle products, 14 griddle sizes, 16 griddle sizes, 18 griddle sizes and 20 griddle sizes to get the makepan values. optimal. The method applied by the Campbell Dudek and Smith (CDS) algorithm, CDS is a method used in flowshop scheduling developed from Johnson's rule which is able to minimize the makespan of 2 machines arranged in series. The CDS method is very suitable for production characters who apply machine sequences to the production process. CDS produces several iterations that have the value of makespan, from those iterations, the minimum value of makespan is to determine the order of products to be produced. This research resulted in an application that can schedule products to be produced by machines automatically. From the test results with a total production of 12 pieces on each product with 6 repetitions, the minimum value of makespan is 210.12 minutes with a sequence of product works 20 pans, 18 pans, 16 pans, 14 pans, and 12 pans. Accuracy of results Application testing shows 99.99% for the first time and 99.96% for the second time when compared to manual calculations